Reformulation of the Monitoring on Political Party Fund System; A Case of Indonesian Political Party System - Muhammad Aljabar Putra; Rezky Panji Perdana Martua Hasibuan; Indra Rahmatullah (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract:A political party is an entry point to affirm the Democratical State. In order to realize the function, political party needs operational fund so that the state-issued Government Regulation Number 1 of 2018 concerning Financial Aid to Political Party which raised financial assistance to political party from 108 rupiahs per valid vote to 1,000 rupiahs per valid vote. However, it became polemic because of increasing political party aid fund without supervision of the management and reporting of aid fund. As a result of the absence of supervision, there is corruption in political party because the supervision of management, reporting of political party fund and sanction have not been done optimally so that political party is not able to accommodate and realize the principles of Good and Clean Governance as mentioned in Law Number 2 Year 2011 concerning Political Party. The purpose of this research is to answer the polemic of increasing political party budget related to the system of monitoring political party fund comprehensively. The method used is juridical-normative with legislation and conceptual approach.Keywords: Political Party, Fund System, DemocracyAbstrak:Partai politik merupakan entry point dalam menegaskan kehidupan Negara Demokrasi. Dalam rangka mewujudkan fungsi tersebut partai politik membutuhkan dana operasional sehingga negara mengeluarkan Peraturan Pemerintah Nomor 1 Tahun 2018 tentang Bantuan Keuangan Kepada Partai Politik yang menaikan bantuan dana partai politik dari Rp.108 per suara sah menjadi Rp.1000 per suara sah. Namun menjadi polemik adalah kenaikan jumlah dana bantuan partai politik tersebut tanpa diimbangi dengan pengawasan terhadap pengelolaan dan pelaporan dana tersebut. Akibat tidak adanya pengawasan tersebut rawan terjadinya praktik korupsi dalam partai politik karena selama ini pengawasan pengelolaan, pelaporan dana partai politik dan sanksi belum dilakukan secara maksimal sehingga belum mengakomodir dan mewujudkan prinsip-prinsip Good and Clean Governance sebagaimana yang diatur dalam Undang-Undang Nomor 2 Tahun 2011 tentang Partai Politik. Tujuan penelitian ini dimaksudkan untuk menjawab polemik kenaikan anggaran partai politik secara komprehensif terkait sistem pengawasan dana partai politik. Metode penelitian adalah yuridis-normatif dengan pendekatan perundang-undangan (statute approach) dan konseptual (conceptual approach). Kata Kunci: Dana Partai Politik, Demokrasi, dan Good Clean GovernanceАннотация :Политические партии являются отправной точкой в утверждении жизни демократического государства. Чтобы реализовать эту функцию, политическим партиям нужен оперативный фонд. В связи с этим, государство издало Постановление правительства № 1 от 2018 года о финансовой помощи политическим партиям по увеличению фонда политических партий со 108 рупий до 1000 рупий за один действительный голос. Однако, проблемой стало то, что увеличение количества финансовой помощи политическим партиям не было сбалансировано с наблюдением за управлением и отчётностью этих фондов. В результате отсутствия такого наблюдения имеются тенденции к коррупционной деятельности в политических партиях, потому что всё это время наблюдение за управлением, отчётность о фондах политических партий и санкции осуществляются неоптимально. Все вышеперечисленные причины ещё не соответствуют и не реализуют принципы честного и надлежащего управления (Good and Clean Governance), урегулированные в Законе № 2 от 2011 года о Политических партиях. Целью данного исследования является решение вопроса увеличения бюджета политических партий в полном объёме, который связан с системами наблюдения за фондами политических партий. Метод данного исследования - юридическо-нормативный подход, законодательный подход и концептуальный подход.Ключевые Слова: Фонд политических партий, демократия, честное и надлежащее управление